(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Bharangi (Clerodendrum serratum) holds a significant place in Ayurvedic medicine, with extensive references in classical texts such as Charaka Samhita, Sushruta Samhita, and Ashtanga Samhita, collectively known as the Brihat Trayi. This critical review delves into the traditional uses and therapeutic applications of Bharangi as documented in these ancient texts, alongside an examination of contemporary scientific research. Emphasizing its role in managing respiratory ailments, inflammatory diseases, and other health conditions, the review aims to explore the use of Bharangi in Samhita kala and enlighten the different formulations where Bharangi is used as one of the Ingredients. This paper seeks to provide a comprehensive understanding of Bharangi’s medicinal potential and enlist the formulations that include Bharangi in it.